In situ Transmission Electron Microscopy observation of Ag nanocrystal evolution by surfactant free electron-driven synthesis - Longo, Elson [UNESP]; Avansi, Waldir; Bettini, Jefferson; Andrés, Juan; Gracia, Lourdes (Springer Nature, 2016)
The study of the interaction of electron irradiation with matter and the response of the material to the passage of electrons is a very challenging problem. However, the growth mechanism observed during nanostructural evolution appears to be a broad and promising scientific field in nanotechnology. We report the in situ TEM study of nanostructural evolution of electron-driven silver (Ag) nanocrystals through an additive-free synthetic procedure. Observations revealed the direct effect of the electron beam on the morphological evolution of Ag nanocrystals through different mechanisms, such as mass transport, site-selective coalescence, and an appropriate structural configuration after coalescence leading to a more stable configuration. A fundamental understanding of the growth and formation mechanisms of Ag nanocrystals, which interact with the electron beam, is essential to improve the nanocrystal shape-control mechanisms as well as the future design and study of nanomaterials.